The effectiveness of urban agriculture as a survival strategy among Gweru urban farmers in Zimbabwe - Hungwe, Chipo (Urban Agriculture Magazine, 2016)
The Nyanga Declaration signed by municipal authorities in 2002 represented a turning point in Zimbabwe as its accommodation and official recognition of urban agriculture heralded a change in the attitude of municipalities. Urban agriculture has great potential to improve household food security and survival, but as long as municipal initiatives only officially accommodate it without providing proper facilitation, like rearrangement and reallocation of resources, urban agriculture will continue to face many challenges.